Revisiting the Radiobiology of Targeted Alpha Therapy - Pouget, Jean-Pierre; Constanzo, Julie (Frontiers in Medicine, 2021)
Targeted alpha therapy (TAT) using alpha particle-emitting radionuclides is in the spotlight after the approval of 224RaCl2 for patients with metastatic castration-resistant prostate cancer and the development of several alpha emitter-based radiopharmaceuticals. It is acknowledged that alpha particles are highly cytotoxic because they produce complex DNA lesions. Hence, the nucleus is considered their critical target, and many studies did not report any effect in other subcellular compartments. Moreover, their physical features, including their range in tissues (<100µm) and their linear energy transfer (50-230 keV/µm), are well characterized. Theoretically, TAT is indicated for very small-volume, disseminated tumors (e.g. micrometastases, circulating tumor cells). Moreover, due to their high cytotoxicity, alpha particles should be preferred to beta particles and X-rays to overcome radiation resistance. However, clinical studies showed that TAT might be efficient also in quite large tumors, and biological effects have been observed also away from irradiated cells. These distant effects are called bystander effects when occurring at short distance (<1mm), and systemic effects when occurring at much longer distance. Systemic effects implicate the immune system. These findings showed that cells can die without receiving any radiation dose, and that a more complex and integrated view of radiobiology is required. This includes the notion that the direct, bystander and systemic responses cannot be dissociated because DNA damage is intimately linked to bystander effects and immune response. Here, we provide a brief overview of the paradigms that need to be revisited.